Doña Genoveva Núñez Herrera: The Ayacucho retablo from another place - Calderón Salazar, Mario Andrés (2025)
This paper studies the variations and contributions of master artist Genoveva Núñez Herrera to the Ayacucho retablo of the XXI century, identifying the elements of her oral tradition, life and personality that have pervaded into her visual work and characterized her artistic style. Additionally, delving into the professional aspect of the marriage Jesús Urbano Rojas – Genoveva Núñez Herrera, the present document contributes to the understanding of the Master-Disciple relationships and its symbiotic dynamics in the Andean folk artist workshop in general and the Retablo workshop in particular.